2022
DOI: 10.1128/msystems.00336-22
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Developmental Exposure to Oxycodone on Gut Microbiota and Relationship to Adult Behaviors and Metabolism

Abstract: This is the first work to show in a rodent model that in utero exposure to an opioid drug can lead to longstanding effects on the gut microbiota when examined at adulthood. Further, such bacterial changes are associated with metabolic host responses. Given the similarities between rodent and human microbiomes, it raises cause for concern that similar effects may become evident in children born to mothers taking oxycodone and other opioid drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
0
10
1
Order By: Relevance
“…Importantly, this study is the first to use a clinically-relevant administration protocol that recapitulates the opioid use profile of pregnant women, including both prenatal and gestational opioids, pulsatile dosing, and increased dosing through pregnancy to account for tolerance. In addition, although previous studies generally report changes in Lachnospiraceae (Grecco et al, 2021), Lactobacillus , Ruminococcus , Allobaculum (Abu et al, 2021), and Clostridia (Lyu et al, 2022), all of which were also altered in the current study, those studies are limited in scope, typically sampling offspring at one age (Grecco et al, 2021; Lyu et al, 2022) or timepoints limited to weaning (Abu et al, 2021) when the gut microbiota composition is still in flux as a result of diet change. Our studies are the first to report that opioid-induced gut microbiota dysbiosis is not only present during early life, but is maintained into adulthood.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Importantly, this study is the first to use a clinically-relevant administration protocol that recapitulates the opioid use profile of pregnant women, including both prenatal and gestational opioids, pulsatile dosing, and increased dosing through pregnancy to account for tolerance. In addition, although previous studies generally report changes in Lachnospiraceae (Grecco et al, 2021), Lactobacillus , Ruminococcus , Allobaculum (Abu et al, 2021), and Clostridia (Lyu et al, 2022), all of which were also altered in the current study, those studies are limited in scope, typically sampling offspring at one age (Grecco et al, 2021; Lyu et al, 2022) or timepoints limited to weaning (Abu et al, 2021) when the gut microbiota composition is still in flux as a result of diet change. Our studies are the first to report that opioid-induced gut microbiota dysbiosis is not only present during early life, but is maintained into adulthood.…”
Section: Discussionmentioning
confidence: 83%
“…typically sampling offspring at one age (Grecco et al, 2021;Lyu et al, 2022) or timepoints limited to weaning (Abu et al, 2021) when the gut microbiota composition is still in flux as a result of diet change. Our studies are the first to report that opioid-induced gut microbiota dysbiosis is not only present during early life, but is maintained into adulthood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysbiosis of the maternal gut microbiota during pregnancy has increasingly been associated with dysbiosis in neonates. 29 , 31 , 32 To determine the impact of gestational opioid exposure on neonatal gut microbiota, fecal samples from the offspring of methadone-exposed or control dams were collected. After quality control of raw sequencing, 445,631 unique ASVs were identified among all samples (Supplemental Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with several studies, which have reported alterations in the gut microbiome with prenatal and early neonatal opioid exposure. 29–31 , 66 Both brief 29 and chronic opioid exposure 30 , 31 , 66 have previously been reported to induce maternal and neonatal microbial dysbiosis. While these studies differed on their reports of alpha diversity, with some reporting increased alpha diversity per Chao 1 index 30 , 66 and others reporting no difference in this metric, 29 , 31 all studies documented profound changes in microbial composition apparent at weaning, 29 , 66 adolescence, 30 and adulthood.…”
Section: Discussionmentioning
confidence: 99%